Urbanization and nature-based tourism development: A case of tourism corridor in Surakarta-Karanganyar-Magetan - Rahayu Paramita (BIO Web of Conferences)
Urbanization and tourism development are closely intertwined, influencing each other in multiple ways and affecting the environment and natural resources both positively and negatively. Therefore, understanding the relationship between the two is crucial for devising strategies that promote more sustainable urban and tourism development. This study aims to examine the interaction between the urbanization process and nature-based tourism. The research questions are: How do urban centers relate to nature-based tourism, and what challenges do nature-based tourism face amid the expansion of urbanization and tourism activities? This study employs GIS mapping and secondary data processed with descriptive statistics, as well as Focus Group Discussions (FGD). The results indicate that urban centers play a central role in coordinating tourism development in the study area. The primary driving forces behind rapid urbanization stem from shifts in major economic sectors from primary (agriculture) to secondary (industrial activities) and tertiary (services) sectors. Subsequently, nature-based tourism contributes to the urbanization process through the development of service activities that to a certain extent cause land conversion in the area of tourism villages, which impacts the sustainability of the main attractions of nature-based tourism. Therefore, effective management of rapid urbanization and tourism development, particularly through land management, is critical for achieving sustainable strategies for interactions between nature-based tourism and urbanization.